The Influence of Bank Mandiri's Entrepreneur Expo in Increasing the Spirit of Entrepreneurship at the 25th Anniversary in West Java Province - Hilma Farhani; Muhamad Ammar Muhtadi (Westscience Press, 2023)
This research investigates the impact of Bank Mandiri's Entrepreneur Expo on the spirit of entrepreneurship during its 25th Anniversary celebration in West Java Province. Employing a mixed-methods approach, we assess the influence of the expo on attendees' entrepreneurial spirit through quantitative surveys and gain deeper insights into their experiences and perceptions via qualitative interviews. The quantitative analysis reveals that expo attendees exhibit significantly higher levels of motivation, willingness to take risks, innovation, and intention to start a business compared to non-attendees. Qualitative findings highlight the expo as an inspirational platform that offers networking opportunities, knowledge acquisition, and a confidence boost. Overall, Bank Mandiri's Entrepreneur Expo emerges as a significant catalyst for fostering entrepreneurship, providing valuable lessons for organizations and policymakers seeking to promote entrepreneurship and innovation within their communities.